2020
DOI: 10.22146/ijc.57012
|View full text |Cite
|
Sign up to set email alerts
|

Design of New Quinazoline Derivative as EGFR (Epidermal Growth Factor Receptor) Inhibitor through Molecular Docking and Dynamics Simulation

Abstract: Erlotinib, Afatinib, and WZ4002 are quinazoline derivative compounds and classified as first, second, and third-generation EGFR inhibitor. All inhibitors have been given directly to cancer patients for many years but find some resistance. These three compounds are candidates as the lead compound in designing a new inhibitor. This work aims to design a new potential quinazoline derivative as an EGFR inhibitor focused on the molecular docking result of the lead compound. The research method was started in buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Thus, there was no significant change in terms of the SASA values of the complexes during the simulation. Overall, the values of both RoG and SASA values showed that the structures of EGFR-xanthone-chalcone complexes were relatively stable during the molecular dynamic simulations for 100 ns, which was in agreement with the other works [7,14,[58][59][60].…”
Section: Molecular Dynamics Of Xanthone-chalcone Derivativessupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, there was no significant change in terms of the SASA values of the complexes during the simulation. Overall, the values of both RoG and SASA values showed that the structures of EGFR-xanthone-chalcone complexes were relatively stable during the molecular dynamic simulations for 100 ns, which was in agreement with the other works [7,14,[58][59][60].…”
Section: Molecular Dynamics Of Xanthone-chalcone Derivativessupporting
confidence: 90%
“…Computer-aided drug design offers a powerful tool to design and screen new chemotherapy agents [6][7]. In this in silico assay, the crystalline structure of protein receptors inside the cancer cells is modeled and simulated in the presence of a new chemotherapy agent [8].…”
Section: ■ Introductionmentioning
confidence: 99%